2022
DOI: 10.11591/edulearn.v16i4.20455
|View full text |Cite
|
Sign up to set email alerts
|

BioPhy magazine based on a floating market for problem-solving skills and environmental awareness

Abstract: This study aimed to describe the validity and effectiveness of the floating market-based BioPhy magazine to improve problem-solving skills and encourage students to conduct environmental awareness campaigns. This research was development research with Tessmer formative evaluation model. The field test subjects were 24 students who studied fluids in the Fundamental Physics Course in the 2021/2022 academic year. Data were obtained through validation sheets and problem-solving questions. Data were analyzed quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Floating markets significantly contribute to riverbased culture, being viewed as a part of ecotourism and river culture rather than merely a tourist destination [66]. Initially, people came to see guava, golden apple, and other Agro-based products sold in floating boats in Atghar and Kuriana, oblivious to the rich background and cultural history.…”
Section: Discussionmentioning
confidence: 99%
“…Floating markets significantly contribute to riverbased culture, being viewed as a part of ecotourism and river culture rather than merely a tourist destination [66]. Initially, people came to see guava, golden apple, and other Agro-based products sold in floating boats in Atghar and Kuriana, oblivious to the rich background and cultural history.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research conducted Ref. [7]- [9] found that character education had a significant impact on environmental awareness among students. The character education program helped increase students' knowledge and awareness of environmental issues and motivated them to participate in environmental preservation activities.…”
Section: Introductionmentioning
confidence: 99%